Evaluating the impact of Rht hypomorphic mutations in durum wheat. Issue 1 (31st December 2021) - Brown, McKenna M.; Martin, John M.; Jobson, Emma M.; Hogg, Andrew C.; Carr, Patrick M.; Giroux, Michael J.
Abstract: Increasing the yield of wheat ( Triticum spp.) requires identifying new allelic combinations by crossing or by creating useful variation in yield limiting genes. Wheat yield is impacted by many factors, including tiller number and seeds per tiller, both of which are impacted by the Reduced height ( Rht ) gene. Durum wheat [ T. turgidum L. subsp. durum (Desf.) van Slageren] varieties are either standard height, wild type for Rht ( Rht‐B1a ), or are semidwarf and carry the Rht‐B1b allele. Rht‐B1b increases productive tillers but can result in plants too short for easy harvest in the northern United States and shorter coleoptiles that reduce dry soil germination. In this study, durum plants varying for Rht alleles created by ethyl methanesulfonate (EMS) mutagenesis were studied to determine the impact of each allele upon agronomic and seed traits. The projects' goal is to increase durum wheat yield through the development of a plant with height intermediate between current full‐height and semidwarf varieties. Experiments included field trials, coleoptile length and gibberellic acid (GA) responsiveness assays, and an in vitro test to determine the impact of each Rht mutation upon binding to Gibberellin Insensitive Dwarf1 (GID1). It was found that the Rht‐B1b‐E529K allele conferred plant height and coleoptile length intermediate between Rht‐B1b and Rht‐B1a containing plants, while two Rht‐A1 alleles had lesser impacts with trends toward intermediate‐height plants. The results of this research demonstrate that hypomorphic Rht alleles that alter Rht binding to GID1 may prove useful in optimizing durum wheat height to increase yield across different growing conditions. Core Ideas: Rht hypomorphic alleles result in intermediate plant height. Rht‐A hypomorphic mutations reduce plant height. Intermediate‐height plants carrying hypomorphic Rht alleles have longer coleoptiles.